2003
DOI: 10.1002/art.11059
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Fcγ receptor IIA polymorphism in the antiphospholipid syndrome: An international meta‐analysis

Abstract: Objective. To assess the impact of the Fc␥RIIA-R/ H131 polymorphism on the risk for antiphospholipid syndrome (APS), both primary and secondary to systemic lupus erythematosus (SLE).Methods. This international meta-analysis combined data from 9 research teams. Fc␥RIIA-R/H131 genotypes were determined in 481 APS cases (206 with primary APS), 1,420 SLE controls, and 1,655 diseasefree controls. Data were combined using fixed-effects and random-effects models.Results. Compared with disease-free controls, the RR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 61 publications
2
25
0
1
Order By: Relevance
“…Carlsson et al and Atsumi et al studied 100 white patients with aPL and they found that none of the clinical manifestations of primary APS (arterial or venous thrombosis, recurrent pregnancy loss, and thrombocytopenia) was significantly correlated with the His 131 Arg FcRIIA polymorphism. However, in a more recent meta-analysis (Karassa et al, 2003) a significant increase in Arg 131 homozygosity was found in APS patients and the authors suggested a complex genetic background underlying the relationship between the FcRIIA Arg 131 His polymorphism and APS as a composite of two different and opposing influences with regard to susceptibility. Unfortunately, the number of APS patients with specific clinical manifestations was too small to reliably assess the effect of the FcRIIA polymorphism on the risk of vascular thromboses or other APS-related features.…”
Section: Polymorphisms In Platelet Fcreceptor Iiamentioning
confidence: 98%
“…Carlsson et al and Atsumi et al studied 100 white patients with aPL and they found that none of the clinical manifestations of primary APS (arterial or venous thrombosis, recurrent pregnancy loss, and thrombocytopenia) was significantly correlated with the His 131 Arg FcRIIA polymorphism. However, in a more recent meta-analysis (Karassa et al, 2003) a significant increase in Arg 131 homozygosity was found in APS patients and the authors suggested a complex genetic background underlying the relationship between the FcRIIA Arg 131 His polymorphism and APS as a composite of two different and opposing influences with regard to susceptibility. Unfortunately, the number of APS patients with specific clinical manifestations was too small to reliably assess the effect of the FcRIIA polymorphism on the risk of vascular thromboses or other APS-related features.…”
Section: Polymorphisms In Platelet Fcreceptor Iiamentioning
confidence: 98%
“…A proinfl ammatory genotype, defi ned by polymorphisms in the genes for IL-1 b , TNF a , TGF b , IL6, and toll-like receptor 4 ( tlr4 ), was identifi ed in a clinically affected individual within a family that was multiplex for aPL [ 49 ] . The FcgRIIA-R/H131 polymorphism has been found to be an important determinant of predisposition to APS in a large international meta-analysis that investigated 481 patients with APS and 3,075 control patients (approximately half healthy controls and half with lupus) [ 50 ] . This association was most strongly noted for patients with secondary APS, however, suggesting that lupus might be playing a role in this association [ 50 ] .…”
Section: Human Leukocyte Antigen (Hla) Associationsmentioning
confidence: 99%
“…The FcgRIIA-R/H131 polymorphism has been found to be an important determinant of predisposition to APS in a large international meta-analysis that investigated 481 patients with APS and 3,075 control patients (approximately half healthy controls and half with lupus) [ 50 ] . This association was most strongly noted for patients with secondary APS, however, suggesting that lupus might be playing a role in this association [ 50 ] . Since lupus-like autoimmunity is characterized by ineffective clearance of infl ammatory residue by myeloid cells, a polymorphism in an immunoglobulin receptor found on these cells might have relevance for the persistence of aPL in susceptible individuals.…”
Section: Human Leukocyte Antigen (Hla) Associationsmentioning
confidence: 99%
“…A meta-analysis of the Fcγ IIa receptor polymorphisms suggests that the H131 allele may be associated with APS [23]. The binding of IgG2 with H131 allele may result in a prothrombotic state with increased platelet and endothelial cell activation.…”
Section: Genetic Associationsmentioning
confidence: 99%